(untitled) (Patan Pragya, 2022)
Mass media is a potential agent in the empowerment of women. It influences their social, political and economic dimensions. As a result, they become capable of encountering constraints that come across their way of development process. Effective communication has the potential to enhance women’s quality of life, protect them in the fragile environment and create a knowledge-based society that is more responsive to change and development issues. It can lead to the empowerment of women, enabling them to take control of their lives and participate as equal to men in development. Art and science of using information to one’s own advantage is the key to influence the society. In today’s world, mass media occupies an important place in socialization. It has contributed to emergence of public opinions and public images on important issues in the mass society. Major modern medium is the television—the foremost source of communication even for poor and illiterate people. Indeed, television is a prestigious, powerful and empowering tool that can raise awareness, generate interaction and increase knowledge. Although television is not generally available to communities in very isolated rural areas, increasingly in many developing countries itis becoming a reality even in the countryside. In fact, television plays a significant role in socialization of community’s members - influencing their attitude, performance and manner.